Unveiling Differences in Seismic Response: Comparative Study of Equivalent Linear and Nonlinear Analyses in the Central Coastal Region of Bengkulu, Indonesia - Anggraini, Giovanny Dhebby; Mase, Lindung Zalbuin; Supriani, Fepy; Misliniyati, Rena; Amri, Khairul; Chaiyaput, Salisa (Journal of the Civil Engineering Forum, 2025)
Seismic response analysis is a key aspect in earthquake geotechnical engineering, as it provides important insights into the behavior of soils when exposedtoseismic forces. This research compares equivalent linear and non-linear models in the central coastal region of Bengkulu, which is known for its complex geology and high seismicity. By evaluating the accuracy and reliability of each model in predicting ground motion amplification, this research aims to provide useful recommendations for seismic design. The research method uses one-dimensional equivalent linear and nonlinear propagation modeling, namely Pressure Dependent Hyperbolic (PDH). The analysis resulted in the parameters of Peak Ground Acceleration (PGA), time history acceleration, spectral response acceleration, and amplification factor. The equivalent linear method consistently produced higher values for peak ground acceleration (PGA), spectral response acceleration, time history acceleration, and amplification factor compared to the nonlinear method. The analysis results show that the equivalent linear PGA values are in the range of 0.32g to 0.63g, while the nonlinear values range from 0.20g to 0.52g. The resulting spectral responses are averaged over the design spectrum within 0.2 s to 0.9 s, which can affect low- to high-ceilinged buildings. The equivalent linear amplification factor has a range of 1.59 to 1.91, while the nonlinear has a range of 0.80 to 1.59. Both methods have their advantages, with the nonlinear approach offering greater accuracy for large seismic events, while the equivalent linear model remains useful for preliminary analysis. Hopefully, these findings will improve the understanding of ground response in coastal areas and provide valuable data for improving infrastructure resilience in earthquake-prone areas around the world.